Molecular epidemiology and antibiotic resistance pattern of Enteropathogenic Escherichia coli isolated from bovines and their handlers in Jammu, India - Rehman, Majueeb U; Rashid, Mohd; Sheikh, Javeed Ahmad; Bhat, Mohd Altaf (Journal of Advanced Veterinary and Animal Research, 2014)
The study was aimed to investigate the molecular epidemiology and antibiotic resistance pattern of Enteropathogenic Escherichia coli (EPEC) in bovines and their handlers in Jammu, India. A total of 173 samples comprising of 103 fecal samples from bovines (60 from cattle and 43 from buffaloes), 28 stools and 42 fingertip rinses from bovine handlers were collected during August 2011 to March 2012. The isolated 126 E. coli strains (86 from bovines and 40 from handlers) belonged to 25 different serogroups in addition to rough and untypeable strains. Using multiplex polymerase chain reaction, four EPEC strains were isolated; two each from bovines and their handlers, of which two possessed the hemolysin (hlyA) gene. The prevalence of EPEC was recorded as 1.66% (n=1/60) in cattle, 2.32% (n=1/43) in buffaloes, and 2.85% (n=2/70) in their handlers. Antibiogram studies with the EPEC revealed the presence of multi-drug resistant E. coli. The isolates were mostly resistant to Amikacin, Amoxicillin, Cefixime and Streptomycin, and sensitive to Chloramphenicol. This study indicates that bovines as well as their handlers in Jammu region harbor EPEC, many of which being multi-drug resistant and carrying the hemolysin gene could be of high pathogenic potential for humans. http://dx.doi.org/10.5455/javar.2014.a30